Pengembangan E-Comic “Bimanah” (Belajar Ingat Kisah Muhammad Membangun Kota Madinah) sebagai Media Pembelajaran untuk Kelas 4 SD - Agustin, Lisna; Nabila, Tsania Qisma; Rahmatunisa, Anggun Mutiara; Aeni, Ani Nur (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2025)
Abstract This study aims to develop and analyze the effectiveness of the voice-enabled e-comic "BIMANAH" as a learning medium for elementary school students in studying the history of Prophet Muhammad SAW in building the city of Madinah. This media is designed to enhance student engagement and understanding through attractive illustrations and supporting audio narration. The research method used is development and development (D&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). During the implementation phase, the e-comic was tested on 4th-grade elementary students and evaluated by teachers and media experts based on their comprehension and responses to the media used.The results indicate that this voice-enabled e-comic significantly improves students' understanding of Islamic history compared to conventional methods. Students demonstrated high enthusiasm in using this media as it is more engaging and easily accessible. Teachers also responded positively, as this media aids in delivering lessons more effectively and reduces student boredom. Therefore, the use of technology in Islamic education can be an effective and enjoyable alternative, especially in teaching Islamic history to elementary school students.